Tactile Hypersensitivity and “Overwhelming Subjectivity” in the Touch Experience of People With Congenital Deafblindness: Implications for a Touch-Based Pedagogy - Costain, Kirsten (Frontiers in Education, 2020)
Tactile hypersensitivity, sometimes referred to as tactile aversion, shyness or defensiveness, is a frequently cited challenge for support partners and educators in working with people with congenital deafblindness (CDB). Touch is the most fundamental of the sensory modalities, rivaling other modalities in complexity and an essential building block of emotional, psychological, social, and intellectual development. Though touch hyper-sensitivity can be a significant barrier to such development, tactual sensitivity can be a resource as touch becomes more motivating and accessible for the person with CDB. This article introduces the notion of “overwhelming subjectivity” in the tactual perception of people with CDB and touch hypersensitivity, with a starting point in Katz’s conceptualization of the psychophysiological bipolarity of touch in his pioneering work of 1925 (2016). Though the dual subjective–objective nature of touch has been described by others, Katz’s description is one of the neuro-psychological interface of touch perception at the lowest levels of awareness. This article links Katz’s phenomenology to that of Merleau-Ponty (1968, 2012) to provide a new way of imagining touch hypersensitivity in CDB, and briefly relates this to practical approaches already familiar to support partners. Helping to overcome the deprivation and isolation caused by the overwhelming activation of tactual subjectivity that occurs in touch hyper-sensitivity is an important goal for the partners of people with CDB. The notion of overwhelming subjectivity offers a provocative and novel way of recasting an old and often apparently intractable barrier in CDB that can be useful in thinking about and working with it in the support of people with CDB and other forms of multiple disability and touch hyper-sensitivity.